The complete guide to referencing and avoiding plagiarism - Neville, Colin (Open UP study skills., 2016)
The Complete Guide to Referencing and Avoiding Plagiarism is essential reading for all students and professionals who need to use referencing in academic writing to reflect their own ideas, constructively apply the work of others, and to avoid plagiarism.